Simulation of the two-dimensional infrared spectroscopy of peptides using localized normal modes - Hanson-Heine, Magnus W.D.; Husseini, Fouad S.; Hirst, J.D.; Besley, Nicholas A. (American Chemical Society, 2016)
Non-linear two-dimensional infrared spectroscopy (2DIR) is most commonly simulated within the framework of the exciton method. The key parameters for these calculations include the frequency of the oscillators within their molecular environments and coupling constants that describe the strength of coupling between the oscillators. It is shown that these quantities can be obtained directly from harmonic frequency calculations by exploiting a procedure that localizes the normal modes. This approach is demonstrated using the amide I modes of polypeptides. For linear and cyclic diamides, and the hexapeptide Z-Aib L-Leu-(Aib)2-Gly- Aib-OtBu, the computed parameters are compared with those from existing schemes, and the resulting 2DIR spectra are consistent with experimental observations. The incorporation of conformational averaging of structures from molecular dynamics simulations is discussed, and a hybrid scheme wherein the Hamiltonian matrix from the quantum chemical local-mode ap- proach is combined with fluctuations from empirical schemes is shown to be consistent with experiment. The work demonstrates that localized vibrational modes can provide a foundation for the calculation of 2DIR spectra that does not rely on extensive parameterization and can be applied to a wide range of systems. For systems that are too large for quantum chemical harmonic frequency calculations, the local mode approach provides a convenient platform for the development of site frequency and coupling maps.